Information Management in SMEs: challenges and opportunities - Pessoa, Cláudio Roberto Magalhães (2022)
Influenced by the COVID-19 pandemic, SMEs face unprecedented challenges. Innovation becomes central to facing the crisis and its socio-economic consequences and promoting a sustainable recovery. Aimed in this objeticve, the information and the digital technologies are essential and must be part of the companies response to facing these challenges.This work aims to address information management practices and the transforming potential of technologies in organizations, with a focus on SMEs. Based on a literature review, proposals for actions will be presented to promote efficient and technologically mediated information management, which values information at all stages of its life cycle, and support managers in the decision-making process and in the definition of business strategy